The Position of Inhaled Chemotherapy in the Care of Patients with Lung Tumors: Clinical Feasibility and Indications According to Recent Pharmaceutical Progresses - Rosière, Rémi (Cancers (Basel), 2019)
Despite new treatment modalities, including targeted therapies and checkpoint inhibitors, cytotoxic chemotherapy remains central in the care of patients with lung tumors. Use of the pulmonary route to deliver chemotherapy has been proved to be feasible and safe in phase I, Ib/IIa and II trials for lung tumors, with the administration of drug doses to the lungs without prior distribution in the organism. The severe systemic toxicities commonly observed with conventional systemic chemotherapy are consequently reduced. However, development has failed in phase II at best. This review first focuses on the causes of failure of inhaled chemotherapy. It then presents new promising technologies able to take up the current challenges. These technologies include the use of a dry powder inhaler or a smart nebulizer with advanced drug formulations such as controlled-release formulations and nanomedicine. Finally, the potential position of inhaled chemotherapy in patient care is discussed and some indications are proposed based on the literature.